The Impact of Board Characteristics and Director Ownership on Real Earnings Management: Malaysian Evidence - Rahayu ABDUL RAHMAN; Naimah AHMAD YAHYA; Mohd Taufik MOHD SUFFIAN; Maheran ZAKARIA (Communications of International Proceedings, 2020)
The main objectives of this study is to investigate how board characteristics and director ownership affect real earnings management. In this study, we specifically examine how board size, board independence, duality role and director ownership influence real earnings management practices of Malaysian listed firms. Consistent with prior research, this study uses three proxies to measure real earnings management; abnormal cash flow from operations, abnormal production costs and abnormal discretionary expenses. Using a sample of 1,878 firm-year observations from 2000 to 2007, the results show that board independence and director ownership are significantly negative associated with proxies of real earnings management. Duality role, however, is not associated with real earnings management.
Keywords: board characteristics; managerial ownership; real earnings management; Malaysia.